DOES LIQUIDITY AND FIRM SIZE AFFECT PROFITABILITY? A PANEL DATA ANALYSIS ON FIRM OF CONSUMER NON-CYCLICAL SECTOR - Dewi Maya Sari; Mislinawati (RADJA PUBLIKA, 2023)
The goal of this study is to examine how profitability is impacted by liquidity and firm size. The data utilized is 214 of observation from the 2016–2020 financial reports of manufacturing companies in the consumer non-cyclical sector. Using return on assets (ROA) as a measure of profitability,current ratio as an indicator of liquidity and total assets as indicator of firm size. Panel data analysis using a fixed effect model approach is the empirical methodology used. The findings indicate that liquidity has a positif impact on profitability, while firm size has a negative impact. This research implied in order to make decisions and implement policies that have an impact on effective production and improved performance of firms, management of the firm must monitor and regulate changes in the value of liquidity and firm size.